Polymers as Encapsulating Agents and Delivery Vehicles of Enzymes - da S. Pereira, Adejanildo; Souza, Camila P. L.; Moraes, Lidiane; Fontes-Sant’Ana, Gizele C.; Amaral, Priscilla F. F. (Polymers, 2021)
Enzymes are versatile biomolecules with broad applications. Since they are biological molecules, they can be easily destabilized when placed in adverse environmental conditions, such as variations in temperature, pH, or ionic strength. In this sense, the use of protective structures, as polymeric capsules, has been an excellent approach to maintain the catalytic stability of enzymes during their application. Thus, in this review, we report the use of polymeric materials as enzyme encapsulation agents, recent technological developments related to this subject, and characterization methodologies and possible applications of the formed bioactive structures. Our search detected that the most explored methods for enzyme encapsulation are ionotropic gelation, spray drying, freeze-drying, nanoprecipitation, and electrospinning. α-chymotrypsin, lysozyme, and β-galactosidase were the most used enzymes in encapsulations, with chitosan and sodium alginate being the main polymers. Furthermore, most studies reported high encapsulation efficiency, enzyme activity maintenance, and stability improvement at pH, temperature, and storage. Therefore, the information presented here shows a direction for the development of encapsulation systems capable of stabilizing different enzymes and obtaining better performance during application.